Emergency powers in a time of pandemic / Alan Greene. - Greene, Alan (Law teacher) (Bristol University Press, 2020)
How do we maintain core values and rights when governments impose restrictive measures on our lives? Declaring a state of emergency is the best way to protect public health in a pandemic but how do these powers differ from those for national security and economic crises? This book explores how human rights, democracy and the rule of law can be protected during a pandemic and how emergency powers can best be ended once it wanes. Written by an expert on constitutional law and human rights, this accessible book will shape how governments, opposition, courts and society as a whole view future pandemic emergency powers.